Compulsory Efficient Use of Land (CEUL) for Land Zoning can contrive the rapid change of land use pattern: A Case Study of Charchartala Union, Ashuganj, Brahmanbaria - Bakaul, Mohammad Moniruzzaman (2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.